The Concept of Love for the Homeland from the Perspective of KH Hasyim Asy’ari and Relevance with Social Studies Education - Lila Agustin Triana Sari; Moh Sutomo (heritage, 2022)
The flow of information exchange in the era of globalization that is easily accessed by the young generation makes it easy to accept foreign cultures without being selective and forgetting their own culture. This phenomenon is a factor in weakening the level of love for the student's homeland. Efforts to foster an attitude of love for the homeland in the school environment are by instilling the values of love for the homeland of KH Hasyim Asy'ari through social studies subjects. This research aims to (1) describe the concept of love for the homeland from the perspective of KH Hasyim Asy'ari, (2) describe the relevance of the concept of love for the homeland from the perspective of KH Hasyim Asy'ari with social studies education. The research method used a qualitative approach to the type of library research. Collecting data in this research used the documentation method. Then the data were analyzed by content analysis—the data validity technique used theoretical triangulation. The results of the study show that (1) the concept of love for the homeland from the perspective of KH Hasyim Asy'ari is called Hubbul within minal iman which contains religious values and nationalism values that are implied in the Jihad Resolution as proof of KH Hasyim Asy'ari's commitment and form of nationalism, (2) the relevance of the concept of love for the homeland from the perspective of KH Hasyim Asy'ari with social studies education, which is relevant to the objectives of social studies learning and relevant to the content of the social studies curriculum for VIII Grade in KD 3.4. Analyzing chronology, change, and spatial continuity (geographical, political, economic, educational, social, cultural) from the colonial period to the growth of the national spirit and IX Grade in KD 3.4 Analyzing the chronology, change and continuity of space (geographic, political, economic, educational, social, cultural) from the beginning of independence to the front of reform.